2009
DOI: 10.1038/jcbfm.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

TAT-Hsp70-Mediated Neuroprotection and Increased Survival of Neuronal Precursor Cells after Focal Cerebral Ischemia in Mice

Abstract: Cerebral ischemia stimulates endogenous neurogenesis within the subventricular zone and the hippocampal dentate gyrus of the adult rodent brain. However, such newly generated cells soon die after cerebral ischemia. To enhance postischemic survival of neural precursor cells (NPC) and long-lasting neural regeneration, we applied the antiapoptotic chaperone heat shock protein 70 (Hsp70) fused to a cell-penetrating peptide derived from the HIV TAT to ensure delivery across the blood-brain barrier and the cell memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 83 publications
(49 citation statements)
references
References 32 publications
2
46
0
1
Order By: Relevance
“…In this context, we have previously shown that in vitro transduction of NPCs with TAT-Bcl-x L is efficient and results in sustained neuroprotection against stroke after intracerebral transplantation of TAT-Bcl-x L -transduced NPCs [19]. Although Hsp70-induced neuroprotection has been shown before [10,[52][53][54], this study shows for the first time that the fusion protein TAT-Hsp70 enhances resistance of NPCs against hypoxic-hypoglycemic injury. Since neuroprotection by the TAT domain itself has been described in vitro recently [55,56], we used TAT-HA as a negative control in order to exclude effects of the TAT domain itself on cell viability, neurosphere formation rates, NPC numbers, and differentiation patterns of NPCs.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…In this context, we have previously shown that in vitro transduction of NPCs with TAT-Bcl-x L is efficient and results in sustained neuroprotection against stroke after intracerebral transplantation of TAT-Bcl-x L -transduced NPCs [19]. Although Hsp70-induced neuroprotection has been shown before [10,[52][53][54], this study shows for the first time that the fusion protein TAT-Hsp70 enhances resistance of NPCs against hypoxic-hypoglycemic injury. Since neuroprotection by the TAT domain itself has been described in vitro recently [55,56], we used TAT-HA as a negative control in order to exclude effects of the TAT domain itself on cell viability, neurosphere formation rates, NPC numbers, and differentiation patterns of NPCs.…”
Section: Discussionmentioning
confidence: 68%
“…In order to promote survival of grafted cells, NPCs were protein-transduced with the chaperone Hsp70, which reduces apoptosis and inflammation after hypoxic-ischemic injury [23,24]. Since cellular entry of Hsp70 is poor, transduction was achieved in vitro using the membrane-permeable and neuroprotective TAT-Hsp70 fusion protein before transplantation [10,35]. This study has explicit meaning for future cell-based stroke therapies, since it highlights the importance of cell transplantation routes, implying different mechanisms by which transplanted NPCs induce poststroke neuroprotection.…”
Section: Introductionmentioning
confidence: 99%
“…The neuroprotective effect of HSP against ischemic stroke has been clearly demonstrated in transgenic mice models of HSP70 (Plumier et al 1997;Lee et al 2001;Tsuchiya et al 2003;Lee et al 2004;van der Weerd et al 2005) and HSP27 (van der Weerd et al 2010). Pharmacologic induction or intravenous administration of HSP70 also decreased the extent of infarct in rodent models of stroke (Lu et al 2002;Doeppner et al 2009;Zhan et al 2010). In addition to its role as a chaperone, the underlying neuroprotective function of HSP can also largely be explained by its anti-apoptotic properties and immune modulation (Joly et al 2010;Lanneau et al 2010).…”
mentioning
confidence: 99%
“…It is also possible that Hsp70 induction may stimulate other systems that are responsible for cell survival after brain injury (Seidberg et al 2003;Robinson et al 2005). Cumulative indirect effects of Hsp70, such as suppression of apoptosis (Tidwell et al 2004), lysosome stabilization (Kirkegaard et al 2010), stimulation of the innate immune response (Johnson and Fleshner 2006;Gong et al 2009), suppression of the early preoligomeric stages of Aβ self-assembly (Evans et al 2006;Calderwood 2010), inhibition of proinflammatory signaling (Rozhkova et al 2010), and increase of survival of endogenous neural progenitor cells (Doeppner et al 2009) may account for the observed correlation. Possibly, Hsp70 induction somehow activates other compensatory mechanisms that facilitate regeneration and help to restore for some time normal functioning of neurons after the injury.…”
Section: Discussionmentioning
confidence: 99%